2021
DOI: 10.3390/su13094799
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fourteen Bread Wheat (Triticum aestivum L.) Genotypes by Observing Gas Exchange Parameters, Relative Water and Chlorophyll Content, and Yield Attributes under Drought Stress

Abstract: Water scarceness is a major threat to wheat productivity under changing climate scenarios, especially in arid and semi-arid regions. However, growing drought-tolerant wheat genotypes could be a sustainable option to enhance wheat productivity under drought stress conditions. The aim of this study was to evaluate the effect of mild to severe drought stress on gas exchange parameters, relative water content, SPAD-chlorophyll value, and yield-related parameters of 14 wheat genotypes being cultivated in arid to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 50 publications
(58 reference statements)
6
40
0
2
Order By: Relevance
“…Hence, it is indicated that the wheat grains of BAW 1167, BARI Gom 26, and BAW 1158 dried quickly and attained physiological maturity earlier as compared to BAW 1169. The sigmoid way involving accumulation of dry matter under DS has also been reported earlier [69,89]. The DS condition leads to reduced plant growth, which is reflected in plant height, leaf area, dry weight, and other growth functions [42,90], reduced Chl content, photosynthetic rate, and TDM [14,39,91].…”
Section: Spike Dry Matter (Sdm)supporting
confidence: 62%
See 1 more Smart Citation
“…Hence, it is indicated that the wheat grains of BAW 1167, BARI Gom 26, and BAW 1158 dried quickly and attained physiological maturity earlier as compared to BAW 1169. The sigmoid way involving accumulation of dry matter under DS has also been reported earlier [69,89]. The DS condition leads to reduced plant growth, which is reflected in plant height, leaf area, dry weight, and other growth functions [42,90], reduced Chl content, photosynthetic rate, and TDM [14,39,91].…”
Section: Spike Dry Matter (Sdm)supporting
confidence: 62%
“…The results indicated that genotypes BAW 1169 and BAW 1158 were relatively less affected by water deficit stress than the other two genotypes. DS leads to reduced plant growth reflected in leaf area, dry weight, spike length, number of grains spige −1 and grain weight [39,42,89,90]. High Chl content under DS indicates lower intensity of photosynthetic apparatus's photo-inhibition, therefore decreasing losses of carbohydrates for grains development [95].…”
Section: Dry Weight Of Grains Spike −1mentioning
confidence: 99%
“…For example, a recent study in wheat showed a positive correlation between grain yield and photosynthetic rate at the heading and grain filling stage (Yu et al, 2020). A similar result in wheat grown under well-watered conditions was also reported by Wasaya et al (2021).…”
Section: Introductionsupporting
confidence: 75%
“…For example, the high concentrations of salt in saline habitats Agronomy 2021, 11, 1193 2 of 16 make it difficult for roots to absorb water from the soil. Drought reduces morphological traits such as the reduction of leaf size and vegetative growth, and physiological traits such as the reduction of photosynthesis and stomatal conductance, and alters the anatomical characteristic of the stem [1,2].The results of these stresses induce an excessive production of reactive oxygen species (ROS), which cause extensive cell damage and inhibition of photosynthesis [3,4]. To these stresses are added the deficits of inorganic nutrients, the residues of chemicals such as herbicides and pesticides used in normal agricultural practice and heavy metals present in the earth's crust that emanate from industrial activities [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%